Morphological and Physiological Plasticity of Spinal Lamina II GABA Neurons Is Induced by Sciatic Nerve Chronic Constriction Injury in Mice - Zhang, Hongmei; Li, Yan; Yang, Qing; Liu, Xian-Guo; Dougherty, Patrick M. (Frontiers in Cellular Neuroscience, 2018)
Transgenic mice expressing enhanced green fluorescent protein (EGFP) at the γ-aminobutyric acid (GABA) synthesizing enzyme glutamic acid decarboxylase 67 (GAD67) locus were used to test whether the morphological properties of these neurons show plasticity with nerve injury. Whole-cell patch-clamp was used for intracellular labelling and to physiologically characterize EGFP-expressing lamina II neurons in spinal cord slices from sham and CCI mice. As well, whole cell recordings were made of non-EGFP labelled cells to ascertain changes in overall inhibitory signaling following CCI. The EGFP labelled neurons in both sham and CCI mice exhibited islet, central and vertical cell morphological profiles but no radial cell profiles were observed. The length of cell dendrites was found to be significantly shorter in CCI mice for all cell profile types. The longest neurites averaged 155.96 ± 18.29 µm in CCI mice compared to 334.93 ± 29.48 µm in sham control mice. No change was observed in either passive or evoked membrane properties of EGFP-expressing neurons in CCI versus sham mice. Meanwhile, the frequency of miniature inhibitory post-synaptic currents of non-EGFP expressing spinal lamina II neurons was significantly reduced. These results suggest that reduced inhibitory output from GABA neurons occurs with nerve injury in part due to altered cell morphology.